ChemInform Abstract: Copper‐Catalyzed Reaction of Ketenimine and in situ Generated Immonium Ion: Access to α, β‐Unsaturated Amidines. Issue 30 (29th July 2014) - Yao, Bangben; Shen, Chuang; Liang, Zunjun; Zhang, Yuhong
Abstract The presented three component reaction provides a mild and efficient access to a wide variety of unsaturated amidines of which some might be useful for pharmacological application.